High Performance Flexible Organic Electrochemical Transistors for Monitoring Cardiac Action Potential. Issue 19 (14th August 2018) - Liang, Yuanying; Ernst, Mathis; Brings, Fabian; Kireev, Dmitry; Maybeck, Vanessa; Offenhäusser, Andreas; Mayer, Dirk
Abstract: Flexible and transparent electronic devices possess crucial advantages over conventional silicon based systems for bioelectronic applications since they are able to adapt to nonplanar surfaces, cause less chronic immunoreactivity, and facilitate easy optical inspection. Here, organic electrochemical transistors (OECTs) are embedded in a flexible matrix of polyimide to record cardiac action potentials. The wafer‐scale fabricated devices exhibit transconductances (12 mS V −1 ) and drain–source on‐to‐off current ratios (≈10 5 ) comparable to state of the art nonflexible and superior to other reported flexible OECTs. The transfer characteristics of the devices are preserved even after experiencing extremely high bending strain and harsh crumpling. A sub‐micrometer poly(3, 4‐ethylenedioxythiophene) doped with poly(styrenesulfonate) layer results in a fast transport of ions between the electrolyte and the polymer channel characterized by a cut‐off frequency of 1200 Hz. Excellent device performance is proved by mapping the propagation of cardiac action potentials with high signal‐to‐noise ratio. These results demonstrate that the electrical performance of flexible OECTs can compete with hard‐material‐based OECTs and thus potentially be used for in vivo applications. Abstract : Flexible organic electrochemical transistors (OECTs), fabricated in this work, exhibit excellent flexibility and superior transconductance as well as resistance to mechanical deformation. Action potential propagation of cardiac‐like cell is recorded with OECTs embedded in flexible matrix of polyimide. Large signal to noise ratio and biocompatibility pave the way to electrophysiological sensor applications.